Pemaknaan Laba Usaha di Kalangan Pebisnis Keuangan Syariah - Addury, Multazam Mansyur (Institut Agama Islam Negeri Parepare, 2023)
The business world cannot be separated from the amount of profit earned. Profit is used as an important reference in assessing a company, predicting business bankruptcy, and overcoming financial difficulties. Furthermore, profit is often used as the main indicator in assessing the success of a business entity. Based on this, the purpose of this research is to find out the orientation that Sharia financial practitioners want to look for and the meaning of profit among Sharia financial practitioners. The research design used in this study is a qualitative research design with an exploratory approach. The sample to be used in this study amounted to 3 respondents from Sharia financial practitioners in Yogyakarta. The data collection technique used is interview. The data analysis technique used is an interactive analysis model that refers to three stages: data reduction, data presentation, and conclusion drawing and verification. Based on the results of research and discussion, it can be concluded that the orientation that Sharia financial practitioners want to seek is da'wah to introduce to the public financial transactions without usury, to obtain profits, to benefit the people and to prosper members and the community. Sharia financial practitioners understand profit as a result obtained from business activities that are not contrary to Islamic law and mutually beneficial between one party and another and no one is harmed.